ASSISTING THE INTEGRATION OF TECHNOLOGY AND ITS EFFECT ON STUDENTS' ATTITUDES IN DISTANCE LEARNING - Dewi Suriyani Djamdjuri; Iil Hilyatul Kamilah (Jurnal Pemberdayaan Masyarakat dan Inovasi, 2022)
Teaching and learning process can be easily conducted due to technological developments. The development and application of information technology is also beneficial for the world of education. The purpose of this study is to assist in the integration of technology and its influence on students' attitudes in distance learning during the Covid 19 pandemic. The method of conducting this report is qualitatively descriptive study and the implementation of the service is carried out with two stages, that is the first is mentoring and the second is data retrieval through interviews and questionnaires addressed to students. The results of the implementation of this assessment show that there are many technological concerns about student attitudes, and technology can affect students' attitudes positively or negatively. Among the positive influences of technology on students are that it can increase creativity in using technology, feel more curious about technology and can affect the attitude of cooperation in student self-development. As for the negative impact that affects students, students find it quite difficult to understand the material provided by the teacher. The results of the assistances showed that the positive impact was more dominant than the negative impact experienced by students.